2009
DOI: 10.1002/adsc.200800741
|View full text |Cite
|
Sign up to set email alerts
|

Immobilisation of the BINAP Ligand on Dendrimers and Hyperbranched Polymers: Dependence of the Catalytic Properties on the Linker Unit

Abstract: A series of immobilised Carbo-BINAP ligands has been synthesised using poly(propylene imine) (PPI) dendrimers as soluble supports. They contain up to 64 BINAP ligands at their periphery without an additional linking unit. Despite the high steric requirements of the ligand, all dendrimers could be completely functionalised, resulting in the immobilised systems in good yields. Furthermore, the immobilisation strategy that worked out for the fixation of AMINAP ligands with additional linking units as well as of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Only a few other applications of the supported BIN-AP ligands were described, such as a Rh-hydroboration reaction of vinylarenes 13 and Cu-hydrosilylation of acetophenone. 14,15 While the Wilkinson's Ru II -BINAP complex was very effective in the hydrogenation of olefins, the same catalyst was not very active for the hydrogenations of ketones. Noyori had shown that the association with a stoichiometric amount of 1,2-diphenylethylenediamine (DPEN) accelerates the hydrogenation of ketones by a metal-ligand bifunctional catalysis mechanism.…”
Section: The Binap Ligandsmentioning
confidence: 98%
“…Only a few other applications of the supported BIN-AP ligands were described, such as a Rh-hydroboration reaction of vinylarenes 13 and Cu-hydrosilylation of acetophenone. 14,15 While the Wilkinson's Ru II -BINAP complex was very effective in the hydrogenation of olefins, the same catalyst was not very active for the hydrogenations of ketones. Noyori had shown that the association with a stoichiometric amount of 1,2-diphenylethylenediamine (DPEN) accelerates the hydrogenation of ketones by a metal-ligand bifunctional catalysis mechanism.…”
Section: The Binap Ligandsmentioning
confidence: 98%
“…Supplementary data related to this article can be found online at doi: 10.1016/j.jorganchem.2011. 11.026.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Studies by number of groups further established the effectiveness of dendritic catalysts. Astruc [9] and co-workers, and Gade [10] and co-workers demonstrated a negative dendritic effect in CeC bond forming reactions and hydrogenation reactions, respectively. On the other hand, Majoral and co-workers [11] showed a positive dendritic effect with phosphorous containing dendrimer in selected organometallic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides molybdenum-, iron-, and zinc-based systems the application of copper can be beneficial. Indeed, the potential of copper catalyst in reduction techniques has been explored in the reduction of various functionalities [46][47][48][49][50][51][52][53][54][55][56][57][58]. However, the catalytic reduction of sulfoxides in the presence of copper has been so far unreported, while the converse process has been studied [59].…”
Section: Introductionmentioning
confidence: 97%